A blinded, randomized and controlled multicenter field study investigating the safety and efficacy of long-term use of enflicoxib in the treatment of naturally occurring osteoarthritis in client-owned dogs - Homedes, Josep; Ocak, Marion; Riedle, Sebastian; Salichs, Marta (Frontiers in Veterinary Science, 2024)
Background: Enflicoxib is a Cox-2 selective NSAID shown to be efficacious and safe in the treatment of pain and inflammation associated with canine osteoarthritis (OA) in clinical studies of six weeks duration.Objective: This prospective, multisite, blinded, randomized, placebo-controlled, parallel-group field study aimed to confirm the safety and efficacy of enflicoxib in long-term canine OA treatments.Animals: A total of 109 client owned dogs with clinical and radiographic signs of OA for at least 3 weeks were enrolled with 78 dogs completing all study visits. Methods: Dogs were randomized at a 3:1 ratio to receive enflicoxib (n=83) or placebo (n=26) once weekly during six months. Dogs underwent veterinary assessments from Day 0 to Day 189 using a clinical sum score (CSS). Efficacy was also assessed by the owners using the Canine Brief Pain Inventory (CBPI). Safety was assessed clinically and by repeated blood and urine sample analysis. The efficacy outcome measure was the treatment response according to the CSS and secondarily the treatment response according to the CBPI. The primary safety outcome was the incidence of adverse events and secondarily the evolution of the clinical pathology parameters.Results: Percentages of CSS responders for enflicoxib were 71.6%; 74.6% and 71.6% on Days 44, 135 and 189 respectively, always showing statistically significant differences (p<0,05) vs placebo (41.7%; 33.3% and 20.8% respectively). Treatment response according to owner assessments followed the same pattern, achieving significant differences compared to placebo after two weeks of treatment. The incidence and type of adverse events were as described in previous enflicoxib studies of shorter duration and as for other NSAIDs, with no tendency to increase over time. No relevant changes in haematology, biochemistry or urine parameters were observed.Enflicoxib safety and efficacy profile is maintained after a long-term treatment, which together with its weekly administration, makes it a good alternative for the chronic treatment of dogs with naturally occurring osteoarthritis.